PERANCANGAN SISTEM INFORMASI AKUNTANSI PEMBELIAN DAN PERSEDIAAN - Purwoko, Purwoko (Bina Nusantara University, 2010)
Procurement and inventory is important activities in a company. Therefore it is the aim of this article to design an accounting information system for procurement and inventory of office supplies to help in fast and accurate planning and decision making. Methods used to collect required data and information is library research and field research. Design and analysis method used is analysis using Object Oriented Analysis and Design. From observation results it is obtained that transaction records in the company is still conducted manually and inefficient in keeping records of incoming and outgoing goods. It is concluded that a computerized procurement and inventory information system would help the management in decreasing faults and increasing the current system effectively.Keywords: accounting information system, procurement, inventory, office supplies.